The Influence of Online Shopping on Lazada E-Commerce on Rational Consumer Behavior of the Millennial Generation in Tangerang - Amiruddin, M. Ruslan; Alwan, Sobari; Riswanto, Wendy Eko; Fantini, Endah (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The online buying habits of millennials have shed light on how this generation uses e-commerce sites and makes decisions about what to buy. Based on survey data, the millennial generation has unique shopping tastes which are strongly influenced by certain factors. Rational behavior is consumer behavior when purchasing goods that prioritizes logical and general thinking. A quantitative associative approach was used in this research. In other words, the aim of this research is to determine the magnitude of the influence or correlation that exists between two variables. Researchers use a sampling strategy known as non-probability sampling, or sampling by considering many factors. With limited time, the research can be continued and become material for further research studies